Effect of Change Position and Back Massage on Physiological Parameters for Patients with Back Pain Post-Cardiac Catheterization - Kawther Kareem Al-Bayati; Rajha A. Hamza Al-Kassar (Kufa Journal for Nursing Sciences)
Background: Back pain is frequently reported following cardiac catheterization. This is mainly due to the prolonged bed rest prescribed post-cardiac catheterization, ranging from 3 to 6 h (Masoudi et al.,2017).